Chemotherapy related symptoms and symptoms distress of women with breast cancer - Cajucom-Natividad, Loyda Amor L.
Breast cancer is one of the most prevalent cancer among Filipino women and one of its most common medical management is chemotherapy, However, in there are very little local studies that look into the possible chemotherapy-related symptoms and even much lesser local literature on the symptom distress these chemotherapy-related symptoms may bring about. -- Thus, the study aimed to primarily identify the chemotherapy-related symptoms of Filipino women with breast cancer and determine which are perceived to lead to symptom distress. Other objectives includes: a) to determine the intensity of the chemotherapy-related symptoms are perceived to be most distressing; c) describe the perceived indicators of symptom distress of Filipino women with breast cancer; d) determine the relationship between symptom intensity and symptom distress; e) determine the association between modifying factors and the degree of symptom intensity and degree of symptom distress. -- The study utilized the descriptive-correlational research design. The study was conducted at the Breast Care Clinic of a government tertiary hospital in the Philippines. The participants were selected using purposive-criterion sampling wherein the inclusion criteria are: they should be female, 18 y.o. and above, diagnosed with breast cancer and must be undergoing out-patient chemotherapy, with at least one cycle of the chemotherapy done with. Exclusion criteria included patients who may have meet the above criteria but already has a severe condition or complication that may hinder cooperation in an interview. The sample size taken was at 135 Filipino women with breast cancer. The study utilized a descriptive-correlational research design with a sample of 135 patients coming from the out-patient clinic of a tertiary hospital. Data collection tools used were a general information sheet, modified TRSC, modified MSAS and Karnofsky scale. Graphs and Percentage Distribution tables were used to present data while Crosstabulations and Chi-Square Test, Spearman Rank Coefficient and Friedman’s Test were used for the statistical analysis. The study result shows that the ten most common symptoms among women with breast cancer undergoing chemotherapy remain to be alopecia, vomiting, loss of appetite, weakness, sensitive sense of smell, dizziness, taste alterations, nausea, GI pain, headache, mucositis/stomatitis and insomnia. This is out of the 40 symptoms that were reported. These physiological and psychological symptoms that were reported using their local language generated by typology of the symptom that may be used to better understand their expressions of their chemotherapy-related symptoms. It is also evident that there are symptoms that tend to cluster, with alopecia and mucositis having the most number of associated symptoms. -- The ten most distressing symptoms were anxiety related to treatment, pain over insertion site, insomnia, sensitive sense of smell, pain on various body parts, vomiting, GI pain, mucositis/stomatitis, taste alterations and loss of appetite which includes both physiological and psychological symptoms. -- As to how they were able to perceive symptom distress prior to chemotherapy, the women were able to perceive such when the symptom causes anxiety or fear and if it causes a decrease in the ability to perform daily activities. On the other hand, for the chemotherapy-related symptoms, three general indicators of symptom distress can be drawn. Symptom distress is perceived when it causes fear and worrying, if it leads to feelings of negative elf-perception such as sadness, shame and unattractiveness and finally if it leads to inability to function or physical limitations and discomforts. -- The study also revealed that certain symptoms have significant correlation between symptom intensity and symptom distress. During the initial assessment this included pain over the breast, drowsiness, dizziness, GI Pain, Vomiting, and Loss of Appetite (at alpha of .01). However, during follow-up, only 3 of these symptoms remained to show a positive relationship between symptom intensity and symptom distress. These were dizziness, loss of appetite and vomiting. -- With regards to symptom intensity and Karnofsky Performance Scale Score, the symptoms nausea, mood alterations and easy fatigability gave negative associations with it, which indicates that as these symptoms intensify, the functional ability of the participant decreased. -- The study shows that women with breast cancer undergoing chemotherapy may suffer from varying intensity of chemotherapy-related symptoms but this does not necessarily translate to the same degree of symptoms distress for all symptoms. Anxiety over treatment outcomes was a predominant theme in the symptom distress experience of Filipino women with breast cancer. Filipino women’s self expression and description of their symptom is a valuable coping mechanism to have a more accurate assessment of their chemotherapy-related symptoms since they may not be able to directly verbalize psychological symptoms and this may be expressed in directly in their description of their symptoms. -- Chemotherapy-related symptoms do tend to cluster and thus presence of one symptom must prompt assessment of other symptoms.